ANALISIS PENGARUH FAKTOR-FAKTOR MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siarwi Siarwi (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2018)
The purpose of this research is to know the effect of Human Capital element, Structural Capital and Capital Service to Return On Assets (ROA) either partially or simultaneously in banking company that has go public and always make a profit during the period of 2010 - 2014. The research method used is proportionate stratified random sampling, with sample of 22 banks and data obtained from Bank Indonesia. Analysis technique used is multiple regression analysis by using Eviews 7.0 software for regression analysis and hypothesis test, because data used is panel data, that is data that combine time series and cross section data. The results showed that Human Capital Elements have positive and significant impact on Return On Assets (ROA) of 82.69% and the rest of 7.31% influenced by other factors. Structural Capital (Structural Capital) has a positive and significant impact on Return On Assets (ROA) of 81.82%. and the remaining 18.18% influenced by other factors, from the Capital Elements Services (Customer Capital) have a positive and significant impact on Return On Assets (ROA) of 84.50% and the remaining 15.50% influenced by other factors. Based on the results of Eviews output obtained F table of 2.40. Thus Fcount> Ftable (25.74514> 2.40), then seen from the value of Probability (F-statistic) is 0,0000, smaller than 0.05 or 0.000 <0.05, so H0 is rejected and H1 accepted. It is that the variables of Human Capital Elements (Human Capital), Structural Capital (Capital Structural), Capital Capital Service (Customer Capital) simultaneously (together) have a significant influence on Return On Assets (ROA). With multiple regression equation is: Y = 0.015 - 0.00047 X1 + 5.99 X2 + 0.0128 X3